Erratum: Investigation of Feline calicivirus infection in cats with upper respiratory tract disease in Diyarbakir, Turkey - Baksi, Nazan; Simsek, Aynur (Brazilian Journal of Veterinary Research and Animal Science, 2021)
Feline calicivirus is among the most common pathogenic microorganisms in upper respiratory tract disease (URTD) and oral lesions of cats. It leads to stomatitis, oral ulceration, ocular and nasal discharge, conjunctivitis, fever, lameness, anorexia, hypersalivation, pneumonia, respiratory distress, coughing, and depression in infected cats. This study aimed to determine the role of Feline calicivirus (FCV) in cats with the upper respiratory tract disease in the Diyarbakir region, Turkey, to provide treatment for infected cats and contribute to the disease prophylaxis. The study material consisted of 10 cats (control group) considered to be healthy according to the clinical examination and 20 cats with URTD that were not vaccinated against Feline calicivirus infection of different breeds, ages, and genders brought to Dicle University Veterinary Faculty Prof. Dr. Servet SEKIN Polyclinic with URTD. After routine clinical examinations of the animals, oral and conjunctival swabs and blood samples were taken. Hematological and biochemical analyzes of blood samples were performed. Swab samples were analyzed by the polymerase chain reaction (PCR) method for the diagnosis of the agent. Oral lesions, hypersalivation, ocular and nasal discharge, coughing, and breathing difficulties were seen in clinical examinations of cats with URTD. Feline calicivirus was detected in only one cat's conjunctival swab sample in PCR analyses. As a result, we found that Feline calicivirus infection was present in cats with URTD in the Diyarbakir region, and 5% positivity was found in cats with clinical symptoms according to PCR analysis.